Construction Of Gene Expression Model On Relationship Between Candida Albicans And Colorectal Cancer - Zhang, Haoling (2024)
This study primarily explores the paradox of whether Candida albicans (C. albicans) promotes or inhibits the development of Colorectal cancer (CRC), focusing on its metabolites mixture for relevant arguments. Differential gene analysis was initially employed to construct a model of differential gene-related prognostic genes (mRNAs) and was internally and externally validated within biological information databases. The impact of metabolites mixture on CRC cell viability was assessed utilizing the CCK-8 assay at different time intervals (12, 24, 48, and 72 hours) and concentrations (OD600 approximately 0.2, 0.3, 0.4). qRT-PCR was employed to assess the mRNA expression levels of prognostic genes EHD4, LIME1, GADD45B, TIMP1, and FDFT1 in each group of CRC cells. Cell invasion and migration capabilities were evaluated through Transwell experiments. Finally, the eATP content was determined using an ATP detection kit. This study identified a total of 213 differentially expressed genes. A prognostic model containing 5 specific mRNA markers, namely EHD4, LIME1, GADD45B, TIMP1, and FDFT1, was constructed. C. albicans metabolites mixture reduced CRC cell activity. qRT-PCR results showed that compared to normal colonic epithelial cells, LIME and EHD4 were downregulated in CRC cells, while FDFT1 expression was significantly upregulated.